Japan Trench event stratigraphy: First results from IODP giant piston coring in a deep-sea trench to advance subduction zone paleoseismology - Michael Strasser; Ken Ikehara; Charlotte Pizer; Takuya Itaki; Yasufumi Satoguchi; Arata Kioka; Cecilia McHugh; Jean-Noel Proust; Derek Sawyer; J. Everest; L. Maeda; K. Hochmuth; et al. (Marine Geology, 2024)

Association between large neutral amino acids and white matter hyperintensities in middle-aged adults at varying metabolic risk - Cherry Youn; Marie L. Caillaud; Yanrong Li; Isabelle A. Gallagher; Barbara Strasser; Hirofumi Tanaka; Andreana P. Haley (Brain Imaging and Behavior, 2024)

Clonal genomic population structure of Beauveria brongniartii and Beauveria pseudobassiana : Pathogens of the common European cockchafer ( Melolontha melolontha L.) - Chiara Pedrazzini; Stephen A. Rehner; Hermann Strasser; Niklaus Zemp; Rolf Holderegger; Franco Widmer; Jürg Enkerli (Environmental Microbiology, 2024)
Beauveria brongniartii is a fungal pathogen that infects the beetle Melolontha melolontha , a significant agricultural pest in Europe. While research has primarily focused on the use of B. brongniartii for controlling M. melolontha , the genomic structure of the B. brongniartii population remains unknown. This includes whether its structure is influenced by its interaction with M. melolontha , the timing of beetle‐swarming flights, geographical factors, or reproductive mode. To address this, we analysed genome‐wide SNPs to infer the population genomics of Beauveria spp., which were isolated from infected M. melolontha adults in an Alpine region. Surprisingly, only one‐third of the isolates were identified as B. brongniartii , while two‐thirds were distributed among cryptic taxa within B. pseudobassiana , a fungal species not previously recognized as a pathogen of M. melolontha . Given the prevalence of B. pseudobassiana , we conducted analyses on both species. We found no spatial or temporal genomic patterns within either species and no correlation with the population structure of M. melolontha , suggesting that the dispersal of the fungi is independent of the beetle. Both species exhibited clonal population structures, with B. brongniartii fixed for one mating type and B. pseudobassiana displaying both mating types. This implies that factors other than mating compatibility limit sexual reproduction. We conclude that the population genomic structure of Beauveria spp. is primarily influenced by predominant asexual reproduction and dispersal.

The effects of dietary amino acid balance on post-embryonic development in a lubber grasshopper - John Hatle; Connor R. Clark; Parker Agne; Nicholas Strasser; Juliana Arcaro; Emma N. Kordek; Kendal Rogers; Clancy A. Short; Zachary Sahni; Sean Sullivan; Brooke Reams; Selena Halleak (Journal of Insect Physiology, 2023)

Population level variation in reproductive development and output in the golden kelp Laminaria ochroleuca under marine heat wave scenarios - Fiona-Elaine Strasser; Luis Matos Barreto; Soukaina Kaidi; Brahim Sabour; Ester A. Serrão; Gareth A. Pearson; Neusa Martins (Frontiers in Marine Science, 2022)
Thermal tolerance is often interpreted as a species-wide thermal niche in the absence of studies focusing on the adaptive potential of populations to exhibit differential thermal tolerance. Thus, considering intraspecific thermal plasticity, local adaptation or both between populations along distributional gradients when interpreting and predicting species responses to warming is imperative. Removing the effect of environmental histories by raising kelp gametophyte generations in vitro under common garden conditions allows unbiased comparison between population-specific adaptive variation under different environmental conditions. Following this approach, this study aims to detect (potentially) adaptive differentiation in microscopic life-stages (gametophytes) between populations of a temperate forest forming kelp, Laminaria ochroleuca from locations with distinct thermal conditions. Gametophytes from four geographically distinct populations were subjected to different temperature treatments (17, marine heat waves of 23, 25 and 27°C) and gametophyte survival during thermal stress as well as reproductive success and photosynthetic responses during recovery were investigated. Intraspecific variation in resilience and reproductive output to thermal stress was found in L. ochroleuca ; gametophytes from the most northern population (Brittany, France) were the most thermally sensitive, with mortality onset at 23°C, whereas mortality in the remaining populations was only apparent at 27°C. Gametophytes from northern Spain and Morocco exhibited very low reproductive success during recovery from 23 and 25°C. However, when recovering from the highest thermal treatment (27°C) the reproductive development and sporophyte output was higher than in the gametophytes from France and Italy (Mediterranean). The population-specific responses of gametophyte resilience and reproductive success to temperature stress suggest genetic differentiation in response to variation in local thermal regimes.

Tiefenorientierte Pumpversuche zur Bestimmung der hydraulischen Anisotropie in einem geschichteten Grundwasserleiter - Ruth Maier; Carsten Leven; Daniel Strasser; Bernhard Odenwald; Olaf A. Cirpka (Grundwasser, 2022)
Zusammenfassung Die horizontale Schichtung von Sedimentkörpern bewirkt, dass die effektive hydraulische Durchlässigkeit eines sedimentären Grundwasserleiters in horizontaler Richtung größer ist als in der vertikalen, was sich unter anderem auf die Ausbreitung des Absenktrichters bei Grundwasserentnahmen auswirkt. Um die großräumige hydraulische Anisotropie zu bestimmen, führten Maier et al. (2022a) an einem Testfeld am Oberrhein tiefenorientierte Pumpversuche mit einem Förderbrunnen mit drei Filterstrecken durch. Die Grundwasserentnahmen erfolgten nacheinander jeweils aus einer Tiefe. Die Absenkungen aller Versuche wurden in verschiedenen Abständen zum Förderbrunnen und verschiedenen Tiefen gemessen und gemeinsam mit einem Computermodell ausgewertet. In der vorliegenden Arbeit zeigen wir, dass die Interpretation von Absenkkurven bei Entnahme aus nur einer Tiefe zu Durchlässigkeitsbeiwerten führt, die vornehmlich die Bedingungen in der Entnahmetiefe widerspiegeln. Für die Bestimmung vertikaler Unterschiede der hydraulischen Durchlässigkeit und der hydraulischen Anisotropie ist es notwendig, Versuche mit mehreren Entnahmetiefen zu kombinieren. Der Arbeitsaufwand im Feld kann jedoch durch eine optimierte Beobachtungsstrategie reduziert werden.

Guidelines on reporting treatment conditions for emerging technologies in food processing - Vicente M. Gómez-López; Gianpiero Pataro; Brijesh Tiwari; Mario Gozzi; María Ángela A. Meireles; Shaojin Wang; Buenaventura Guamis; Zhongli Pan; Hosahalli Ramaswamy; Sudhir Sastry; Florent Kuntz; Patrick J. Cullen; et al. (Critical Reviews in Food Science and Nutrition, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Revealing vertical aquifer heterogeneity and hydraulic anisotropy by pumping partially penetrating wells - Ruth Maier; Carsten Leven; Emilio Sánchez-León; Daniel Strasser; Maximilian Stoll; Olaf A. Cirpka (Hydrogeology Journal, 2022)
The stratification of sedimentary aquifers introduces spatial variability in hydraulic conductivity, primarily between individual horizontal layers. On larger scales, the vertical heterogeneity enhances hydraulic anisotropy, with the horizontal conductivity typically exceeding the vertical one. In this study, the hydraulic anisotropy of a stratified aquifer is estimated from data of hydraulic tests in which water is sequentially extracted from well sections screened at different depths, and the hydraulic response is measured at various multilevel observation wells. The applicability of the method is demonstrated by field tests in a fluvial gravel aquifer in the Upper Rhine Valley, Germany. A homogeneous anisotropic model, and models with three and five anisotropic layers, are fitted to the measured drawdowns in the steady-shape regime, in which differences in hydraulic head between observation locations do not change over time even though the head values themselves change. The position of the five horizontal layers is based on the lithology of the drilling profile at the pumping-well location. The three-layer model is achieved by merging insensitive or similar layers with sensitive layers. The fits result in estimates of the radial and vertical hydraulic conductivities for all layers of the respective models, which are upscaled to effective parameters over the entire depth in the case of the multilayer models. The homogeneous model shows significantly higher errors than those of the heterogeneous models. The heterogeneous locally anisotropic models not only reveal vertical variability of hydraulic conductivity, but also lead to a three-times larger anisotropy ratio upon upscaling.

Ground speed and planter downforce influence on corn seed spacing and depth - S. A. Badua; A. Sharda; R. Strasser; I. Ciampitti (Precision Agriculture, 2021)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Epistemological dimensions of the water–energy–food nexus approach: reply to discussions of “Challenges in operationalizing the water–energy–food nexus” - C. Cudennec; J. Liu; J. Qi; H. Yang; C. Zheng; A. K. Gain; R. Lawford; L. de Strasser; P. T. Yillia (Hydrological Sciences Journal, 2018)

Internal deformation of a muddy gravity flow and its interaction with the seafloor (site C0018 of IODP Expedition 333, Nankai Trough, SE Japan) - J. S. Laberg; M. Strasser; T. M. Alves; S. Gao; K. Kawamura; A. Kopf; G. F. Moore (Landslides, 2017)

Probabilistic stability evaluation and seismic triggering scenarios of submerged slopes in Lake Zurich (Switzerland) - M. Strupler; M. Hilbe; F. S. Anselmetti; A. J. Kopf; T. Fleischmann; M. Strasser (Geo-Marine Letters, 2017)

Modeling the Effect of the Selective S1P1 Receptor Modulator Ponesimod on Subsets of Blood Lymphocytes - Dominik Lott; Andreas Krause; Christian A. Seemayer; Daniel S. Strasser; Jasper Dingemanse; Thorsten Lehr (Pharmaceutical Research, 2017)

Uncoupled eNOS annihilates neuregulin-1β-induced cardioprotection: a novel mechanism in pharmacological postconditioning in myocardial infarction - Bernd Ebner; Stefan A. Lange; Thomas Eckert; Clementine Wischniowski; Annette Ebner; Rüdiger C. Braun-Dullaeus; Christof Weinbrenner; Carsten Wunderlich; Gregor Simonis; Ruth H. Strasser (Molecular and Cellular Biochemistry, 2013)

Exogenous glycine betaine and proline play a protective role in heat-stressed barley leaves ( Hordeum vulgare L.): A chlorophyll a fluorescence study - A. Oukarroum; S. El Madidi; R. J. Strasser (Plant Biosystems, 2012)

Contributions of high- and low-quality patches to a metapopulation with stochastic disturbance - Carly A. Strasser; Michael G. Neubert; Hal Caswell; Christine M. Hunter (Theoretical Ecology, 2012)

Sediment dynamics and geohazards off Uruguay and the de la Plata River region (northern Argentina and Uruguay) - Sebastian Krastel; Gerold Wefer; Till J. J. Hanebuth; Andrew A. Antobreh; Tim Freudenthal; Benedict Preu; Tilmann Schwenk; Michael Strasser; Roberto Violante; Daniel Winkelmann (Geo-Marine Letters, 2011)

The pro-apoptotic BH3-only protein Bid is dispensable for development of insulitis and diabetes in the non-obese diabetic mouse - Zia U. A. Mollah; Jibran Wali; Mark D. McKenzie; Balasubramanian Krishnamurthy; Kate L. Graham; Stacey Fynch; Joshua Szanyi; Pere Santamaria; Thomas Brodnicki; Janette Allison; Andreas Strasser; Thomas W. H. Kay; et al. (Apoptosis, 2011)

A strong-motion database from the Central American subduction zone - Maria Cristina Arango; Fleur O. Strasser; Julian J. Bommer; Douglas A. Hernández; Jose M. Cepeda (Journal of Seismology, 2011)

Increased P2X7R expression in atrial cardiomyocytes of caveolin-1 deficient mice - K. Barth; C. Pfleger; A. Linge; J. A. Sim; A. Surprenant; N. Steinbronn; R. H. Strasser; M. Kasper (Histochemistry and Cell Biology, 2010)

Limited genetic variation and structure in softshell clams (Mya arenaria) across their native and introduced range - C. A. Strasser; P. H. Barber (Conservation Genetics, 2009)

Foodborne outbreak of hepatitis A, November 2007–January 2008, Austria - D. Schmid; R. Fretz; G. Buchner; C. König; H. Perner; R. Sollak; A. Tratter; M. Hell; M. Maass; M. Strasser; F. Allerberger (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Response of plants to ectomycorrhizae in N-limited conditions: which factors determine its variation? - A. Corrêa; R. J. Strasser; M. A. Martins-Loução (Mycorrhiza, 2008)

Truncation of the distribution of ground-motion residuals - Fleur O. Strasser; Julian J. Bommer; Norman A. Abrahamson (Journal of Seismology, 2008)

The double-resistance-breaking Tomato mosaic virus strain ToMV1-2 contains two independent single resistance-breaking domains - M. Strasser; A. J. P. Pfitzner (Archives of Virology, 2007)

Association of OPRM1 A118G variant with the relative reinforcing value of nicotine - R. Ray; C. Jepson; F. Patterson; A. Strasser; M. Rukstalis; K. Perkins; K. G. Lynch; S. O’Malley; W. H. Berrettini; C. Lerman (Psychopharmacology, 2006)

Are Mycorrhiza Always Beneficial? - A. Corrêa; R. J. Strasser; M. A. Martins-Loução (Plant and Soil, 2006)

Reduced nicotine reward in obesity: cross-comparison in human and mouse - Julie A. Blendy; Andrew Strasser; Carrie L. Walters; Kenneth A. Perkins; Freda Patterson; Robert Berkowitz; Caryn Lerman (Psychopharmacology, 2005)

Apoptosis and autoimmune disease - L. A. O'Reilly; A. Strasser (Inflammation Research, 1999)

The extracellular matrix in hibernating myocardium - a significant factor causing structural defects and cardiac dysfunction - A. Elässer; M. Schlepper; R. Zimmermann; K.-D. Müller; R. Strasser; W.-P. Klövekorn; J. Schaper (Molecular and Cellular Biochemistry, 1998)

Sex Hormones Differentially Regulate Isoforms of UDP-Glucuronosyltransferase - Simone I. Strasser; Sheree A. Smid; Maurice L. Mashford; Paul V. Desmond (Pharmaceutical Research, 1997)

Heterologous protein production in yeast - Gerd Gellissen; Karl Melber; Zbigniew A. Janowicz; Ulrike M. Dahlems; Ulrike Weydemann; Michael Piontek; Alexander W. M. Strasser; Cornelis P. Hollenberg (Antonie van Leeuwenhoek, 1992)